Does the presence of elephant dung create hotspots of growth for existing seedlings?. (20th March 2019) - Kalbitzer, Urs; McInnis, Victoria; Omeja, Patrick A.; Bortolamiol, Sarah; Chapman, Colin A.
Abstract: Megaherbivores play a central role in the evolution and functioning of ecosystems. In tropical forests elephant species are some of the few remaining megaherbivores. Through elephant foraging, nutrients that would be locked in leaves and stems, taking months or years to decay, are quickly liberated for use. In 10 experimental sites in Kibale National Park, Uganda, we set up 10 pairs of plots (4 × 4 m), each pair involved one treatment, elephant dung addition, and one control. After 1 y, we quantified growth (height and leaf number) and survival of young light-demanding (12) and shade-tolerant (19) plant species (439 stems in total). In general, the addition of elephant dung did not increase seedling growth, and it only increased the number of leaves in shade-tolerant plants with a large initial number of leaves. Researchers have speculated that the loss of elephants would shift the composition of African forests to slow-growing tree species. However, this is not supported by our finding that shows some slow-growing shade-tolerant plants grew more new leaves with additional nutrient input from elephant dung, a condition that would occur if elephant numbers increase.